Emission inventory of marine traffic for the Port of Šibenik - Pastorčić, Darko (Array, 2020)
The paper estimates the exhaust emissions of marine traffic in the port of Šibenik. The results of the analysis were obtained by including the following gaseous pollutants: nitrogen oxide (NOX), sulphur oxide (SOX), particulate matter (PM), volatile organic compounds (VOCs) and carbon dioxide (CO2) as greenhouse gas. In order to gain results and estimate the emission of harmful gases in the port of Šibenik, the passenger and the cargo throughput were taken into account. The activities of the ship during which the exhaust gases are emitted into the atmosphere are slow cruising in the reduced speed zone, manoeuvring and hotelling. The “bottom-up” method used in the emission estimation takes into account the ship’s engine power, engine load factor, fuel type, the emission factor, time of cruising and time hotelling in the port of Šibenik. The results of the analysis have shown that approximately 70 % of total emissions come from passenger ships (cruise ships) and 30 % from cargo ships.